Subnational Civil Servant Pension Schemes in Brazil : Context, History, and Lessons of Reform - World Bank (Washington, DC, 2022)
Brazil's pension system takes up an oversized proportion of its social protection spending. It comprises of Regime Geral de Previdéncia Social (RGPS), covering private sector workers, and over two thousand Regimes Pröprios de Previdéncia Social (RPPS), insuring public civil servants at federal and subnational levels. While the total membership of RPPS only stands at about 10 percent of RGPS coverage, its spending amounts to almost half of RGPS pension outlays. This paper attempts to present an integrated view of RPPS pension schemes, their influence on subnational budgets, and their interaction with human resource policies. After a brief introduction, Chapter 3 starts by documenting the history of civil service and its associated pension schemes, looking for explanations on how subnational RPPS became so big, dispersed, and difficult to reform. The fiscal consequences of subnational civil service pension scheme expansion and maturation, including RPPS role in the fiscal challenges and policies of the last few years, are discussed in Chapter 4. Chapter 5 attempts to expose important interlinkages between pension and human resource policies and argues for the need of integrated policy approach. Chapter 6 describes the history of previous RPPS reform attempts, while Chapter 7 focuses on the effects of federal pension reform of 2019 on subnational civil servant pension schemes. The paper ends with lessons and policy recommendations for the future.